PCR-DGGE METHOD FOR MICROFLORA ALTERATION IN SHRIMP DIGESTIVE ORGAN FOLLOWING Lactobacillus ADMINISTRATION - Nunak Nafiqoh; Poh-Shing Chang; Yu-Chi Wang (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
Recently, bacteria as probiotic usage in aquaculture are deeply investigated. Probiotic application in aquaculture leads to alteration in bacteria community within environment and inside digestive system of the host. However, the evidence of treated bacteria presence is very limit. This study was aimed to reveal the effectiveness of PCR-DGGE method to bring some evidence of the applied probiotic existence within aquatic organism. Two species of Lactobacillus were applied in this experiment. Litopenaeus vannamei was used as host for applied bacteria, L. vannamei was reared using natural sea water in the 45 cm x 15 cm x 25 cm aerated glass tank. Twice daily of enriched Artemia were gived as nutrition during experiment. The result showed that Lactobacillus represent higher in treatment group compare with control after 20 days treatment. In the other hand there was no different of bacteria number between two treated Lactobacillus. PCR-DGGE is a rapid and reliable method for bacteria detection within aquatic organism.